Sample and system parameter estimation from local speckle pattern by fully numerically trained deep convolution neural network - Thitiya Seesan; Daisuke Oida; Kensuke Oikawa; Prathan Buranasiri; Yoshiaki Yasuno (My University, 2021)
Deep convolutional neural network (CNN) based estimators for optical coherence tomography (OCT) are presented. The CNN analyze local OCT speckle patterns and estimate the sample’s scatterer density and OCT resolutions. This estimator is intensity invariant, i.e., it does not use the net signal strength of OCT even to estimate the scatterer density. The CNN is trained by a huge training dataset that was generated by a simple simulator of OCT imaging. And hence, the CNN is trained without experimental datasets. The performance of CNN was evaluated by numerically generated OCT images, and good accuracies of the estimation were shown.
Keywords: Optical Coherence Tomography Applications; Photoacoustic and Ultrasonic Imaging; Advanced Fluorescence Microscopy Techniques